Coffee Product Tourism Development Plan In Mekarsari Gambung Village - Chandra Budhi Septyandi; Gundur Leo; Marceilla Suryana; Syifaa Novianti; Rikantini Widiyanti; Sherly Raka Siwi Putri Utomo (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
This article contains the Community Partnership Program (PKM) activities process, the Bandung State Polytechnic (Polban) collaboration with Mekarsari Gambung Village as its partner, which is in its second year. The problems faced by Mekarsari Gambung Village include the lack of competence of human resources in compiling and presenting qualified tourism products and not having adequate promotional tools to market these tourism products to prospective tourists. Solutions to partner problems offered from this PKM activity include preparing tourism products and making digital marketing tools. The output of the compiled PKM activities is in the form of trekking tour packages which are recorded in the form of an electronic guidebook and a website containing comprehensive information about Mekarsari Gambung Village as a tourism destination along with activities that tourists can carry out during their visit.